KESALAHAN MENGERJAKAN SOAL CERITA DALAM PEMBELAJARAN MATEMATIKA - Budiyono Budiyono (PAEDAGOGIA, 2008)
Based on the experiences, many teachers do not feel very successful in teachingstory problems. On the other hand, many students find that story problems are one of themost difficult challenges in mathematics and do not like them. However, there has been noofficial report on the matter, at least in Indonesia. The purpose of the research is toidentify student's errors in doing story problems on fractions, both decimal fractions andusual fractions. The research was conducted in Kota Surakarta, involving students ingrade 6 for twelve elementary schools. Eight essay story problems on fractions weregiven to those students. Then, data about the student's errors in doing story problemswere collected by looking over the student's work thoroughly. After analyzing the data,the research concluded that about half of the students did not answer story problemscorrectly. The data also revealed that story problems involving usual fractions were moredifficult than story problems involving decimal fractions for the students. There was atrend that story problems which include complex calculation were more difficult thanstory problems which include simple calculation.